Supply Chain Risk Analysis In Rattan Woven Exporting Company Using House Of Risk And Analytic Network Process - Amanda Sofiana Sofiana; Ivana Almira Azali; Sugeng Waluyo (Jurnal Ilmiah Dinamika Rekayasa, 2025)
A rattan furniture manufacturing and exporting company faces challenges in its supply chain, especially related to the scarcity of raw materials that hampers the production process. This study aims to identify risks that affect the supply chain of rattan products and exports using indicators from the SCOR model. In addition, this study also aims to design and determine the priority of supply chain risk mitigation strategies, by integrating the House of Risk (HOR) and Analytic Network Process (ANP) methods. The SCOR model is used to identify risks by grouping activities based on five main supply chain processes: plan, source, make, deliver, and return. After that, an assessment is carried out on each risk event, risk cause, and priority risk that has a major impact on the supply chain, using the HOR Phase 1 method. Furthermore, risk mitigation actions are designed using the HOR Phase 2 method, and priority risk mitigation actions are determined based on company criteria, using the ANP method. The results of risk identification show 29 risk events and 30 risk causes. As a solution, 6 risk mitigation actions are designed to overcome these supply chain problems. From the research results, the priority risk mitigation actions recommended to be implemented first by the company are to carry out planning and control of raw material availability.